Relationship between herpes simplex virus-1-specific antibody titers and cortical brain damage in Alzheimer’s disease and amnestic mild cognitive impairment - Mancuso, Roberta; Baglio, Francesca; Agostini, Simone; Agostini, Monia Cabinio; Laganà, Maria M.; Hernis, Ambra; Margaritella, Nicolò; Guerini, Franca R.; Zanzottera, Milena; Nemni, Raffaello; Clerici, Mario (Frontiers in Aging Neuroscience, 2014)
Alzheimer’s disease (AD) is a multifactorial disease with a still barely understood etiology. Herpes simplex virus 1 (HSV-1) has long been suspected to play a role in the pathogenesis of AD because of its neurotropism, high rate of infection in the general population, and life-long persistence in neuronal cells, particularly in the same brain regions that are usually altered in AD. The goal of this study was to evaluate HSV-1-specific humoral immune responses in patients with a diagnosis of either AD or amnestic Mild Cognitive Impairment (aMCI), and to verify the possible relation between HSV-1-specific antibody (Ab) titers and cortical damage; results were compared to those obtained in a group of healthy controls (HC). HSV-1 serum IgG titers were measured in 225 subjects (83 AD, 68 aMCI and 74 HC). HSV-specific Ab avidity and cortical grey matter volumes analyzed by MRI were evaluated as well in a subgroup of these individuals (44 AD, 23 aMCI and 26 HC). Results showed that, whereas HSV-1 seroprevalence and IgG avidity were comparable in the three groups, increased antibody titers (p<0.001) were detected in AD and aMCI compared to HC. Positive significant correlations were detected in AD patients alone between HSV-1 IgG titers and cortical volumes in orbitofrontal (ROI1 RSp0.56; p= 0.0001) and bilateral temporal cortices (ROI2 RSp0.57; p< 0.0001; ROI3 RSp0.48; p= 0.001); no correlations could be detected between IgG avidity and MRI parameters. Results herein suggest that a strong HSV-1-specific humoral response could be protective toward AD-associated cortical damage.